MEDICATED DERMA STICKS FOR SKIN DISORDERS - VENKATESHWARLU.P; SHASHIKALA.P; PURUSHOTHAM RAO.K.; RAVINDERNATH.A; SAGARE PRASHANTH (International Journal of Pharma and Bio Sciences, 2012)
In order to formulate the effective and efficient topical preparation, consideration must be given to the intended purpose. This is directly concerned with the site of action and the desired effect of the preparation. The topical drug delivery systems available for the treatment have several disadvantages like greasiness, inconvenient to store and requires applicator or use of fingertip, which may lead to contamination. Therefore, it was found essential to find an alternative to counter all the above disadvantages effectively and hence in the present work, formulation and development of medicated sticks has been planned with the drug, Clotrimazole that has anti bacterial and anti fungal activity. The preparation and characterization of medicated sticks were carried out in different phases. Phase I studies includes preparation and evaluation medicated derma sticks using the ointment bases with varied concentrations of waxes and incorporation of medicament in the optimized formula by heating and congealing process. Phase II studies includes characterization of prepared medicated sticks for weight variation, thickness, length, size, shape and drug content uniformity. Phase III studies involve in vitro drug diffusion studies by using prehydrated cellophane membrane for 160 minutes in pH 7.4 phosphate buffer. Phase IV studies includes anti microbial studies of prepared formulations by cup plate method. Phase V studies includes Stability studies conducted for a period of six months and FT-IR Spectral analysis conducted. Phase VI studies includes Primary skin irritation studies carried out on rabbits and guinea pigs and in healthy human volunteers showed no sensitization and edema on skin after 72 hrs of application. The results of present study revealed that the prepared medicated sticks of Clotrimazole are convenient, equally effective, without any contamination chances on application and free from skin irritation.